Mix design, mechanical analysis and performance modelling of warm mix asphalt - Abed, Ahmed (2019)
The asphalt industry has been under pressure to reduce its environmental footprint and energy demands to meet current and future sustainability requirements. Warm Mix Asphalt (WMA) has been developed to reduce the environmental impact of asphalt by reducing its production temperatures from the hot range (i.e. ≥160°C) to the warm range (i.e. 100-140°C). The common idea of most WMA techniques is to use additives in order to either reduce bitumen viscosity or reduce bitumen surface tension, which enhances aggregate coating and eventually enables asphalt mixing at reduced temperatures. A robust method to determine a rational reduction in the production temperatures of asphalt, however, is not available so far; but some methods that are thought to be valid exist for certain additives such as the equi-viscous approach. Also, in the case of incorporating Reclaimed Asphalt Pavement (RAP) with WMA (WMRA), it is uncertain what production conditions are suitable for this mix and how best to design these conditions to ensure acceptable performance. Accordingly, the main aims of this research were to understand and analyse the impact of selected WMA additives on bitumen and asphalt properties, develop a rational method to design optimum production temperatures of WMA and WMRA, and deeply investigate the behaviour of these mixtures concerning performance and durability.